Control systems: analysis and design theory / Afaf Rozan Mohd Radzol ... [et al.] - Mohd Radzol, Afaf Rozan; Isa, Iza Sazanita; Baharudin, Rohaiza; Shamsuddin, Sarah Addyani; Chong, Belinda Chiew Meng (UiTM Press, 2025)
This book is designed to introduce the theory of control systems engineering to undergraduate students. The study of control systems engineering is essential for all engineering fields, including electrical, mechanical, aerospace, biomedical, and chemical engineering. It is intended to be used as a supplement to all textbooks on control systems. It may also be used as a textbook in its own right. It consists of seven chapters arranged accordingly to suit the syllabus of control systems for diploma students or higher levels. This book presents less wording but a clear definition throughout all the chapters. There are also many exercises included after each chapter to strengthen students' knowledge in the respective chapters.